Moderate Differences in Feeding Diets Largely Affect Motivation and Spatial Cognition in Adult and Aged but Less in Young Male Rats - Maliković, Jovana; Feyissa, Daniel D.; Hussein, Ahmed M.; Höger, Harald; Lubec, Gert; Korz, Volker (Frontiers in Aging Neuroscience, 2018)
Nutrition can have severe effects on behavior and cognitive processes. Most of the studies related to this use extremely changed diets, such as high fat contents or the exclusion of distinct components needed for normal development and bodily homeostasis. Here we report significant effects of diets with moderate differences in compositions on food rewarded spatial learning in young (3-4 months), middle aged (6-7 months) and aged (17-18 months) rats. Young rats fed with a lower energy diet showed better performance only during aquisition of the spatial task when compared to rats fed with a standard diet. Middle aged rats (6-7 months) fed with a standard diet in the mean performed less good in the spatial learning task, than rats fed with lower energy diet. Similarily, rats fed with a lower energy diet performed better during all training phases when aged, as in a previous test when they were middle aged and fed with a standard diet. This difference could only be partly explained by lower motivation to search for food in the first test. Correspondingly, the variability of individual performance was significantly higher and increased over trials in middle aged rats fed with the standard diet as compared to middle aged rats fed with lower energy diet. Thus, moderate changes in feeding diets have severe effects in food rewarded spatial learning affecting motivation and cognition in elderly and less in young rats. Therefore, nutrition effects upon food rewarded spatial learning and memory should be especially considered in aging studies.